Penerapan Model Pembelajaran Quick On The Draw dalam Meningkatkan Hasil Belajar IPA Siswa - Muhammad Amran; Abdul Hafid; Anniza Yulia Safitri (STKIP Andi Matappa Pangkep, 2023)
The problem of this research is the low science learning outcomes of students. The purpose of this study was to find out the results of students' science learning by applying the quick on the draw learning model for fourth grade students at SD Inpres 6/75 Biru, Tanete Riattang District, Bone Regency. The approach in this research is a qualitative descriptive approach. Subjects in the study were fourth grade students with a total of 25 people consisting of 13 boys and 12 girls. Data collection techniques used are observation, tests and documentation. The results of the study showed an increase. Cycle I achieved the qualification of Enough (C) and cycle II achieved the qualification of Good (B). The conclusion of this study is that applying the quick on the draw learning model can improve students' science learning outcomes in Class IV SD Inpres 6/75 Biru, Tanete Riattang District, Bone Regency.Â Â